Assessing ototoxicity and patients' satisfaction of topical local anaesthesia in myringotomy and ventilation tube insertion. Issue 4 (2nd April 2019) - Marzouk, S; Al-lami, A; Sykes, R; Neumann, C; Nixon, I J
Abstract: Objectives: Animal studies have suggested that exposure of the middle ear to topical local anaesthesia may be ototoxic. This study aimed to report sensorineural hearing outcomes and patients' satisfaction in those who underwent myringotomy and ventilation tube insertion using topical local anaesthesia. Methods: Twenty-nine patients (32 ears) were operated on. Pre- and post-operative audiology findings were compared. A Likert-type questionnaire on treatment satisfaction was completed at the end of the procedure. Results: Median patient age was 55 years (range, 27–88 years). Pre- and post-operative bone conduction pure tone averages were 26.76 dB and 25.26 dB respectively (mean reduction of −1.22 dB, 95 per cent confidence interval of −5.91 to 8.13 dB; p = 0.7538). One ear (3 per cent) had a reduction in pure tone average of 10 dB. Conclusion: The results suggest that sensorineural hearing loss is not a complication of ear exposure to topical local anaesthesia during myringotomy and ventilation tube insertion. The procedure was well perceived.